Concurrent removal of Cr(III), Cu(II), and Pb(II) ions from water by multifunctional TiO2/Alg/FeNPs beads - Nurfatyha Rusydah, Mohamad Shahdad; Lim, Ying-Chin; Kanakaraju, Devagi; Pace, Andrea (Elsevier Ltd., 2019)
The use of multifunctional materials for water remediation is a modern approach where adsorption phenomena and heterogeneous photocatalysis can be applied for the removal of pollutants. Since the ideal remediation system should be able to remove both organic and inorganic pollutants, a crucial aspect to consider is the knowledge of operational parameters affecting the removal process, especially when heavy metal ions are present in concoction as in real systems. Given the proven efficiency of multifunctional TiO2/Alg/FeNPs magnetic beads for the removal of model organic pollutants, this study investigated the possibility to exploit such system ed heavy metals (MHM), specifically Cr(III), Cu(II), and Pb(II) ions, under ultraviolet irradiation at a wavelength of 254 nm. After a preliminary screening on the optimal catalyst loading, operating parameters such as the initial concentration of metal ions, contact and irradiation time, and pH were investigated to optimize the removal of metal ions using response surface methodology (RSM) via Box–Behnken design. Starting from a MHM solution containing 44 ppm of each metal ion, the removal of Pb(II), Cr(III), and Cu(II) ions in the aqueous solution was nearly completed (>98.4%) for all three ions within 72 min of irradiation at almost neutral pH (pH ¼ 6.8). The stability of TiO2/Alg/FeNPs was confirmed by retrieving and reusing the beads in three consecutive cycles of heavy metals removal without observing significant changes in catalyst efficiency.